Invasive Meningococcal Disease due to Nongroupable Neisseria meningitidis—Active Bacterial Core Surveillance Sites, 2011–2016. (15th April 2019) - McNamara, Lucy A; Potts, Caelin C; Blain, Amy; Topaz, Nadav; Apostol, Mirasol; Alden, Nisha B; Petit, Susan; Farley, Monica M; Harrison, Lee H; Triden, Lori; Muse, Alison; Poissant, Tasha; et al.
Abstract: We characterized 22 meningococcal disease cases due to nongroupable Neisseria meningitidis, a rare cause of invasive disease. Disease presentation and severity were similar to those for serogroupable meningococcal disease. However, 7 (32%) patients had complement deficiency or abnormal complement testing results, highlighting the importance of complement testing for nongroupable cases. Abstract : Although nongroupable Neisseria meningitidis rarely causes invasive disease, our analysis of 22 nongroupable cases showed that disease presentation and severity were similar to those for serogroupable meningococcal disease. However, seven (32%) patients, including all of those with documented complement deficiency testing, had a complement deficiency or abnormal complement testing results, highlighting the importance of more routine complement testing for these cases.